Perancangan Antarmuka Pengguna Sistem Informasi Monitoring dan Evaluasi Prakerin berbasis Website menggunakan Metode Human Centered Design (Studi Kasus: SMKN 2 Sragen): User Interface Design of Website-Based Industrial Work Practice Monitoring and Evaluation Information System Using Human Centered Design Method (Case Study: SMKN 2 SRAGEN) - Wiwit Susilo Ningsih; Hanifah Muslimah Az-Zahra; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Industrial work practices (prakerin) are one of the efforts to prepare vocational school students to enter the world of work. Prakerin at SMKN 2 Sragen is supported by an information system that has just handled the organizing function so that it does not cover implementation, monitoring, and evaluation. Therefore, these functions are still carried out manually. The Prakerin Monitoring and Evaluation Information System (SIMEP) is present to complement the existing system in SMKN 2 Sragen. The development of a system requires an interactive user interface design and one of the design methods is Human Centered Design (HCD) which involves humans in every process. HCD is able to produce an interface that is able to answer the needs of users and stakeholders. The resulting user interface design, namely the internship information website, admin dashboard, students, supervisors, and industry supervisors. Interface design, apart from focusing on the appearance of a product, is also related to usability. Usability evaluation using the Heuristic Walkthrough method allows researchers to identify usability problems in the system carefully and generate few false positives. The results of usability testing on the SIMEP interface by domain experts and usability experts found a total of 21 problems and 14 suggestions for improvement from the evaluator